2016
DOI: 10.1002/lary.25883
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acupuncture on postoperative nausea and vomiting after pediatric tonsillectomy: A meta‐analysis and systematic review

Abstract: When acupuncture at PC6 (neiguan) was used to prevent PONV after pediatric tonsillectomy, the risk ratio was significantly lower compared to that of conventional drug therapy. Although further randomized controlled trials are needed, acupuncture at PC6 is considered an economic and effective treatment for emesis after pediatric tonsillectomy. Laryngoscope, 126:1761-1767, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…These reviews have addressed the evidence base for a range of conditions including back and neck pain [911], osteoarthritis [12, 13], nausea [14, 15], dental pain [16], menstrual cramps [17], and infertility [18, 19], among others. However, less is known at a broader scale regarding gross tends in research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…These reviews have addressed the evidence base for a range of conditions including back and neck pain [911], osteoarthritis [12, 13], nausea [14, 15], dental pain [16], menstrual cramps [17], and infertility [18, 19], among others. However, less is known at a broader scale regarding gross tends in research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In a 2016 study, Shin et al evaluated the antiemetic effects of acupuncture in pediatric patients who had undergone tonsillectomies. 17 Their metaanalysis of 8 articles revealed that the incidence of PONV was significantly lower in the patients who received acupuncture treatment compared to the control group who received traditional antiemetic medications. The researchers concluded that administering acupuncture at pericardium 6 (PC6), located 3 fingerbreadths below the wrist on the inner forearm, is safe and effective at reducing PONV in pediatric patients after tonsillectomies.…”
Section: Results Acupuncturementioning
confidence: 99%
“…For example, a 2015 systematic review of randomized trials utilizing wrist acupuncture for postoperative nausea and vomiting in both children and adults found a significant reduction in symptoms and need for rescue antiemetics compared to sham treatment [ 49 ]. Studies involving exclusively pediatric patients remain limited, although a meta-analysis of clinical studies investigating acupuncture for postoperative nausea/vomiting in children following tonsillectomy further supported these findings [ 50 ]. Of note, acupuncture has proven to be well tolerated and safe in the pediatric population.…”
Section: Integrative Medicine For Distressing Symptoms In Criticalmentioning
confidence: 99%